Individual Differences in the Effects of Physical Activity on Classroom Behaviour - Heemskerk, Christina Hubertina Helena Maria; Sumatic, Mirna; Strand, Steve; Malmberg, Lars-Erik (Frontiers in Education, 2022)
Background: Promoting physical activity (PA) in children is associated with a wide range of desired outcomes. With children increasingly not meeting recommended levels of activity, the school setting offers many opportunities to improve this. Increasing children's on-task behaviour is of particular importance to teachers, and while it has previously been suggested that PA can improve classroom behaviour, a consensus on the dose-response relationship of PA content, and its interaction with children's individual differences, is yet to be reached. This study aimed to investigate this relationship more closely and assess the differences between objective and subjective measures of PA intensity. Method: Data was collected from 76 primary school-aged children (M age = 9.3y, SD = 0.7y; 46 females). The PE lesson intervention followed a 3 (intensity: low, medium, high) by 2 (complexity: low, high) within-person design. Children's task-behaviour was observed pre- and post- the intervention PE lesson during 'business as usual' classroom lesson. PA was measured objectively with wrist-worn accelerometer devices for 24 hours before the intervention, and subjectively rated on a five-point Likert scale after each intervention lesson. Results: The results indicated a difference in subjective and objective measures of PA intensity on children's on-task behaviour. Objective measures positively predicted task-behaviour at moderate to high intensities, whereas subjective ratings were beneficial only at sub-maximal intensity. Findings suggested that boys' on-task behaviour improved at higher intensities, whereas girls were also responsive to lower intensity lessons. Less active children showed more improvement in on-task behaviour after a range of lessons, whereas more active children only benefited from the highest intensity lessons. Finally, children exhibiting the highest levels of off-task behaviour improved their on-task behaviour after all intervention lessons. Conclusion: The findings suggest that higher intensities of PA have a generally positive effect on children's subsequent behaviour, although certain individual characteristics make children more responsive to lower PA intensities. Furthermore, passive off-task behaviours were less prevalent after lower-intensity PA. Thus, individual differences, as well as the target behaviour, are important factors to take into account when designing optimal PE lessons for improving classroom behaviour.